2015
DOI: 10.1007/s10971-015-3806-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of citric acid and urea on the structural and morphological characteristics of BiVO4 synthesized by the sol–gel combustion method

Abstract: Micro-sized spherical BiVO 4 photocatalysts composed of nanoparticles were synthesized by the sol-gel combustion method. The effects of citric acid and urea on the structural and morphological characteristics of samples were studied by X-ray diffraction, field emission scanning electron microscopy, N 2 adsorption and desorption and UV-Vis spectroscopy. The photocatalytic activity was evaluated by the photocatalytic degradation of rhodamine B under visible light. The results showed the sphere-shaped BiVO 4 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…All samples exhibit absorption in the visible light range and the steep absorbance edges of all spectra indicate that the visible light absorption is not due to the transition from impurity levels but the band gap transition. 34 The band gap energies ( E g ) of the prepared samples can be calculated from the UV-vis absorption spectra data using the following formula: αhν = A ( hν − E g ) n /2 , where α , ν , A and E g are the absorption coefficient, the light frequency, a constant and the band gap energy, respectively. The value for n is determined by the type of optical transition of a semiconductor ( n = 1 for direct transition and n = 4 for indirect transition).…”
Section: Resultsmentioning
confidence: 99%
“…All samples exhibit absorption in the visible light range and the steep absorbance edges of all spectra indicate that the visible light absorption is not due to the transition from impurity levels but the band gap transition. 34 The band gap energies ( E g ) of the prepared samples can be calculated from the UV-vis absorption spectra data using the following formula: αhν = A ( hν − E g ) n /2 , where α , ν , A and E g are the absorption coefficient, the light frequency, a constant and the band gap energy, respectively. The value for n is determined by the type of optical transition of a semiconductor ( n = 1 for direct transition and n = 4 for indirect transition).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that crystallinity is an important factor to influence photocatalytic activity. Several routes were taken to prepare the BiVO 4 photocatalyst via the wet chemical route, including the solvothermal method, sol–gel synthesis, and hydrothermal synthesis. Morphology control of the BiVO 4 photocatalyst, such as nanotubes, nanoribbons, nanorods, nanofibers, and nanoplates, is extensively studied and indicates that the morphology of the BiVO 4 photocatalyst is a crucial factor for characteristic properties of BiVO 4 . Particularly, the hydrothermal method had been used to synthesize structure-controlled and highly crystalline nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, concave defects with less than ≈2 µm diameter were also noticed (see Figure S2 in the Supporting Information for further details). Thus, a very unique morphology for round-shaped BiVO 4based materials was revealed that is different from the typical solid [22][23][24] or hollow [25][26][27] spheres. Moreover, nitrogen adsorption-desorption measurements were run as well in order to get further insight into their specific surface area (Figure S3, Supporting Information).…”
Section: Synthesis and Characterization Of Bivo 4 Micromotorsmentioning
confidence: 94%